2020
DOI: 10.1108/ijtc-05-2020-0105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tourists’ sociodemographic characteristics on their perception of destination personality and emotional experience of a city break destination

Abstract: Purpose The purpose of this paper is to investigate the influence of tourists’ sociodemographic characteristics on their perception of destination personality and emotional experience on the example of the city break tourism destination. Design/methodology/approach To examine this relationship, survey research was conducted on a sample of 203 national and international tourists who visited Novi Sad, the second-largest city in Serbia. Findings Research results confirmed the role of travelers’ sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 84 publications
3
15
0
Order By: Relevance
“…The results also showed that the influence of these variables on the choice of foreign destinations is more pronounced in respondents belonging to Generation Z compared to the respondents belonging to Generation X, and similar results were obtained in previous research(Robinson & Schanzel, 2019;Yang & Lau, 2015), as well as by the authors who state that the influence of these variables is more pronounced in younger than in older respondents (Beerli-Palacio & Martin-Santana, 2018;Phau et al, 2014). At the same time, the obtained results are different in relation to studies that found that the impact of these variables is more pronounced in older people than in younger people(Šagovnoviš & Kovaţiš, 2020;Tešin et al…”
supporting
confidence: 61%
“…The results also showed that the influence of these variables on the choice of foreign destinations is more pronounced in respondents belonging to Generation Z compared to the respondents belonging to Generation X, and similar results were obtained in previous research(Robinson & Schanzel, 2019;Yang & Lau, 2015), as well as by the authors who state that the influence of these variables is more pronounced in younger than in older respondents (Beerli-Palacio & Martin-Santana, 2018;Phau et al, 2014). At the same time, the obtained results are different in relation to studies that found that the impact of these variables is more pronounced in older people than in younger people(Šagovnoviš & Kovaţiš, 2020;Tešin et al…”
supporting
confidence: 61%
“…Previous research [16,29,30,51] indicates some differences in destination personality perception between respondents of different sociodemographic characteristics, especially of different nationality. The literature also highlights the importance of sociodemographic characteristics (such as gender and race) as a moderator of the relationship between brand personality and consumer satisfaction [52], while specifically, the study by Awad [53] emphasizes the impacts of age, income, and education.…”
Section: Literature Review and Hypotheses Development 21 Travel Desti...mentioning
confidence: 99%
“…Tourist personality is expected to influence activity preferences at destinations. Although the influence of individual characteristics has not been analyzed in the context of activity preferences, the expectation of a positive influence is based on the fact that many authors have demonstrated the influence of tourist personality on behavior [15,16,[90][91][92], with some authors clearly highlighting the influence of tourist personality on tourists' choice of activities [93][94][95]. It should also be noted that the Big Five model has not been widely used so far for tourists, but rather, simplified psychographic models have been applied [96].…”
Section: Activity Preferencesmentioning
confidence: 99%
See 2 more Smart Citations